Shortcomings and Problems of Tourist Destinations in Uzbekistan - Akhmedova Sarvinoz Riskiboy qizi (Genius Publishing Group, 2023)
This article analyzes the tourism potential of our country and issues of tourism development. Also, tasks and measures to be implemented to increase the place and role of tourism in the growth of our economy and the living standard of the population have been determined.
Keywords: Tourism industry; hotels; museum tourism; cultural tourism